PENYULUHAN KESEHATAN GIZI SEIMBANG SEBAGAI TINDAKAN PREVENTIF TERHADAP OBESITAS REMAJA DI DESA KAPEDI KECAMATAN BLUTO SUMENEP - Tawvicky Hidayat; Moh. Wardi; Encung Encung (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
Obesity (over nutrition) is a very dangerous problem that is increasing every year. This is due to the ignorance of adolescents to maintain a lifestyle with balanced nutrition, and also the factor of a lazy lifestyle (lazy to move) which has recently become increasingly entrenched among adolescents. Especially with the existence of